PEMBELAJARAN MENYENANGKAN DI SEKOLAH DASAR DENGAN METODE SARISWARA (KI HADJAR DEWANTARA) DI ERA DIGITAL (GENERASI Z) - Prasetyowati, Dwi Indah; Martini, Sri (Jurnal Sosialita, 2025)
The rapid development of information technology in the digital era has a huge impact on the world of education. Generation Z, who grew up with technological advancements, needs a learning approach that is not only effective, but also engaging and fun. In this context, the Sariswara method created by Ki Hadjar Dewantara has great relevance as it emphasises the harmony between thoughts, feelings and will. This research aims to explore the application of the Sariswara method in learning in elementary schools combined with digital technology to create fun, creative, and effective learning for Generation Z students. This research also examines Ki Sugeng Subagyo and Ki Sutikno's views on the application of technology in education that can support the quality of learning in the digital era. The results show that combining the Sariswara method with technology can create a fun learning experience and increase learners' involvement in the learning process. Kata Kunci: Pembelajaran Menyenangkan, Sariswara, Generasi Z, Era Digital, Teknologi Pendidikan